1999
DOI: 10.1099/0022-1317-80-4-979
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the prDNA and the genomic termini of the gamma2-herpesvirus bovine herpesvirus type 4.

Abstract: The linear virion DNA of bovine herpesvirus type 4 (BHV-4) is flanked by tandem repeats designated polyrepetitive DNA (prDNA). To investigate the structure and functional role of the prDNA for cleavage/packaging of progeny viral DNA, the complete nucleotide sequence (2267 bp) of a cloned prDNA unit of BHV-4 was determined. Moreover, the terminal fragments of the genome and the junctions between prDNA and the central unique DNA were analysed. In order to characterize the function of the prDNA of BHV-4, a transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…A sequence proposed as the HCMV pac2 sequence by Kemble and Mocarski has pac2 sequence characteristics but is located at an unusual position internal to pac1 within the a sequence (18). No sequences with clear pac2-like characteristics are found near the ends found on HCMV concatemers, i.e., near the other end of the a sequence from pac1 or near the terminal end of the c sequence (5,7,18,23,26). Thus, it is not possible to state that HCMV concatemer ends contain pac2 elements but only that pac1-containing ends are absent.…”
mentioning
confidence: 80%
“…A sequence proposed as the HCMV pac2 sequence by Kemble and Mocarski has pac2 sequence characteristics but is located at an unusual position internal to pac1 within the a sequence (18). No sequences with clear pac2-like characteristics are found near the ends found on HCMV concatemers, i.e., near the other end of the a sequence from pac1 or near the terminal end of the c sequence (5,7,18,23,26). Thus, it is not possible to state that HCMV concatemer ends contain pac2 elements but only that pac1-containing ends are absent.…”
mentioning
confidence: 80%
“…The 2,267-nucleotide sequence of a single prDNA element of BoHV-4 strain 66-p-347 was published previously (6). Sequence analysis of this prDNA element showed similarities to the pac-1 and pac-2 consensus sequences of the cleavage and packaging site which is essential for the replication of the viral genome of HSV (14).…”
mentioning
confidence: 99%
“…Analysis of the predicted open reading frames (ORFs) of the prDNA indicated no homology to sequences for known proteins. It was shown that one prDNA element is sufficient for cleavage and packaging and therefore plays a key role in the replication of BoHV-4 (6).…”
mentioning
confidence: 99%
“…In virion DNA the Uc element is adjacent to the L terminus and Ub is adjacent to the S terminus (23). Within the Ub and Uc regions are two domains, defined as pac1 and pac2, respectively, that contain several highly conserved motifs present near the ends of other herpesvirus genomes, including those lacking a terminal redundancy (5,8,9,11). The presence of these conserved sequences near the termini of herpesvirus genomes, the fact that they are brought into close proximity upon circularization, and the fact that in most instances cleavage of concatemeric DNA occurs between the pac1 and pac2 signals led to the suggestion that they have important roles in the cleavage packaging process.…”
mentioning
confidence: 99%
“…This is followed by a T-rich element (pac1 T element) and another region of high GϩC content (pac1 distal GC element). Characteristically, the pac1 T element is flanked by the sequences C n G n from the proximal GC element and G n from the distal GC element, and this unit has been proposed to represent the functional pac1 signal (5,8,11,18). Experiments with deletion mutants removing sequences from either end of the HSV-1 a sequence have shown that regions critical for cleavage and packaging reside within both Ub and Uc (11,22,27,34).…”
mentioning
confidence: 99%